Efectos de dispersión lineal y advección por flujo externo en frentes en propagación - Martínez Rodríguez, Andrés Alfredo (2020)
Kuramoto-Sivashinsky equation in a two dimensional slab with infinite walls and advection by external flow is considered. Stationary front solutions were then found using the shooting method with simple Euler method and oscillatory front solutions were solved with simple Euler method. Numerical results for both were analyzed, finding the solutions for stationary fronts including external flow, Couette and Poiseuille. A modified Kuramoto-Sivashinsky equation, similar to the equation used to described solitary waves was also considered and the effect it had on stationary fronts with and without external flow was also explored. For oscillatory solutions, the front profiles and the phase space diagrams were calculated, a bifurcation diagram was also analyzed for no external flow as well as for fronts advected by Poiseuille and Couette external flow, and good agreement with Feigenbaum’s number was found in all cases.